Identification and molecular characterization of three genetic variants of Grapevine leafroll-associated virus 3 (GLRaV-3) from South African vineyards and their spread in local vineyards - Jooste, Anna Elizabeth Catharina (Stellenbosch : University of Stellenbosch, 2011)
Thesis (PhD (Genetics))--University of Stellenbosch, 2011.